PEMBUATAN KWH METER DIGITAL 1 FASA BERBASIS ARDUINO MEGA 2560 - Afria B, Muhammad Gifar; Winarno, Heru (Vocational School Diponegoro University, 2017)
Muhammad Gifar Afria B, Heru Winarno, in general, a digital kWh meter that can be used to monitor the cosphi value is a 3 phase kWh meter. For 1 phase kWh meters it can only be used to monitor voltage and load usage. In this tool a 1 phase digital kWh meter prototype is made that can be used to monitor cosphi. Cosphi can be compared by comparing voltage and current signals using LM 393 IC. The reading results from IC LM 393 are compared with EX-OR IC so that high signal is obtained when voltage and current have phase difference only. The output of the EX-OR IC is inserted into Arduino to be read and calibrated so that it can be displayed on the LCD. for the process of reading the current magnitude used ACS 712 current sensor, while for the voltage sensor reading step down transformer is used with the principle of voltage divider. In this system, the Arduino MEGA 2560 microcontroller is used as a sensor reading processor that is programmed using the C ++ language so that it can be displayed on a 16x4 LCD. This digital KWH is also equipped with overcurrent protection using a 5vdc relay that is set to work with a driver in the form of an NPN transistor program on Arduino MEGA 2560. In its appearance this tool can provide information in the form of current, voltage, cosphi and the amount of power used in units of time and has been converted into units of rupiah. This tool can help read electrical instrumentation for homes that are still using analog KWH meters. In the process of measuring this device has an error rate of 0% for current reading, 0.4 for voltage reading, 0.07 for cosphi reading and 4.5% for kWh reading.